2011
DOI: 10.1590/s1806-66902011000200032
|View full text |Cite
|
Sign up to set email alerts
|

Predição de ganhos genéticos utilizando o Delineamento I em população de maracujazeiro

Abstract: Resumo -Objetiva avaliar o potencial da população de maracujazeiro em relação às características agronômicas e estimar parâmetros genéticos para fins de predição de ganhos e ainda avaliar as respostas à seleção e os ganhos, a partir das alternativas de seleção. Foram estudadas alternativas de seleção do Delineamento I no maracujazeiro amarelo: seleção entre machos, de fêmeas/machos (todos os machos), entre fêmeas (independente de machos), de fêmeas/machos selecionados, e de seleção combinada. Ficou evidenciada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…As leituras foram feitas em amostras de suco da polpa, extraído por prensagem manual e filtragem em tela de nylon (Neves et al, 2011). A produtividade (kg ha -1 ) foi determinada após colheita e pesagem dos frutos da parcela, nos diferentes tratamentos.…”
Section: Methodsunclassified
“…As leituras foram feitas em amostras de suco da polpa, extraído por prensagem manual e filtragem em tela de nylon (Neves et al, 2011). A produtividade (kg ha -1 ) foi determinada após colheita e pesagem dos frutos da parcela, nos diferentes tratamentos.…”
Section: Methodsunclassified
“…The additive genetic variance is the most important component of the variance, it is the principal cause of similarity between relatives and determining the genetic properties of the population and the response of the population to the selection (Neves et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For all evaluated traits, the coefficients of heritability in the level of males were higher than those in the levels of females and females within those of males; these values varied between 33.59% for STF to 98.37% for PF. High heritability values can occur in traits of little additive genetic variance because they are not much influenced by the environment (Neves et al, 2011). Similarly, de Magalháes Bertini et al (2006 reported that the more elevated broad-sense heritability values, relative to the said traits, indicated greater influence of the non-additive and environmental effects.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, it is important to acquire information, such as estimates of genetic variance components and heritability coefficients, which will support the appropriate choice of breeding strategy as well as enable the estimation of gains from selection (Aguiar, 2003). For a breeder, one considerably important practice is the selection of superior phenotypes of either individuals or families, as acquisition of improved populations requires selection and recombination of individuals or families (Neves et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation